Pembuatan Teknologi Tepat Guna Sarana Cuci Tangan Untuk Pabrik Tahu Di Dusun Bajang - Dhian Satria Yudha Kartika; Christian Ananda Bestari; Annisa Fahmi Lisnamurti; Ashaby Alamsyah; Betrik Muliani; Yesica Arinda Damayanti (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Even though the Covid-19 pandemic has ended, awareness about cleanliness remains an important factor in people's lives. At the tofu factory in Karanglo Village there is no special hand washing area for employees, this certainly supports the spread of disease due to lack of cleanliness. This problem can be overcome by making special hand washing facilities for employees so that cleanliness can be maintained. The method used in this research is the observation method which is done by observing the behavior and activities of a person directly. With the existence of hand washing facilities at the tofu factory in Karanglo Village, it is hoped that it will be able to provide knowledge and insight regarding awareness of maintaining cleanliness and solutions in overcoming the hygienic problems of processed products. Evaluation is carried out by periodic checking to find out whether the tool can function properly. From the activity of making a hand washing station for the tofu factory in Karanglo Village, the factory employees can easily wash their hands both before and after work so that the hygiene of processed products is guaranteed.